(untitled) (Chittagong University Journal of Biological Sciences, 2013)
A total of 197 respondents (129 parents of boys and 68 parents of girls) constituted the sample of the study. To measure mental health status, Bengali version of (Mullick, 2001) Strength and Difficulties Questionnaire (SDQ) was used for the collection of data which was originally developed by Michael Rutter and Robert Goodman. Purposive sampling procedure was used for this purpose. The results showed that about 20.3% students had pro-social problem and 19.3% students were in borderline level in pro-social behavior. Only 0.5% students had Peer problems and 15.7% students were found at borderline level of this problem. About 6.6% students had hyperactivity problem and about 5.6% students were found at borderline level of this problem. About 1.5% students had Emotional symptom problem and 0.5% students were found at borderline level. About 19.3% students had conduct problem and 23.9% students were in borderline level of this problem. About 27.4% students were facing total difficulties problems and 38.1% students were in borderline level. In terms of above all mental health status, boys were found to have more problems than girls. But no significant differences were found between boys and girls at any dimension score or even total difficulties score. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17238 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):119-133, 2011